Severe-to-mild wear transition during running-in of different steel-on-steel tribosystems in ball-on-disc dry sliding reciprocating tests. - Correa Saldarriaga, Pablo Alejandro (2018)
The main motivation of this doctoral thesis is to extend the current knowledge about the tribological behavior of a precipitation-hardenable (PH) austenitic stainless steel (SAE XEV-F or DIN 1.4882), used for manufacturing exhaust valves for internal combustion engines in passenger cars. For this purpose, dry sliding laboratory tests were carried out using this steel and other steels, mainly austenitic and martensitic, used as model materials for the comparative characterization of wear and friction. Experimental tests were conducted using an SRV®4 tribometer in a ball-on-disc configuration with reciprocating movement, in which the discs were the samples and the balls the counter-bodies. Four kinds of steels were tested: a) AISI 310, b) SAE XEV-F, c) AISI H13, and d) Nitrided SAE XEV-F. The ball was made of AISI 52100 bearing steel. The tests were conducted at room temperature and fixed conditions of time (sliding distance) (up to 73.2 m), load (100 N), frequency (10 Hz) and stroke (2mm). Wear was evaluated by means of mass loss in the disc and the ball, and post examination of the worn surfaces. Post examination was conducted using scanning electron microscopy (SEM), coherence correlation interferometry (CCI), and X-Ray diffraction (XRD). Wear debris resulting from tribological interaction were also investigated using SEM and XRD. Additionally, the friction coefficient was measured. High speed filming and interrupted tests were also performed at specific sliding distances. This work reports a severe-to-mild wear transition occurring during the first stage of tribological interaction (running-in) and its relation to the load distribution variation at the interface throughout the tribological tests. The wear transition was observed in different steel-on-steel tribosystems in ball-on-disc contact configuration and occurred due to the combined effects of two factors: a) the contact pressure reduction, due to the increase of nominal contact area caused by wear; and b) subsurface strain hardening (when relevant). The pressure/distance variation was determined experimentally and modeled empirically. Subsurface strain hardening was observable (and measurable) mainly the austenitic steels. Significant differences in wear (and friction) were observed between homogeneous (monophasic) steels and the heterogeneous (multiphasic) SAE XEV-F valve steel. Wear in the homogeneous steels presented an inverse correlation with hardness. Wear on the AISI 310 presented non-linear wear rates for a significant portion of the test. Wear on the SAE XEV-F valve steel was pronounced (even in the mild regime) due to a combined effect of two factors: a) formation of hard debris, which induced an abrasive component to wear by relative sliding, and b) subsurface NbC fracture, which markedly affected the material removal due to plastic deformation in the surrounding matrix. Wear of the nitrided SAE XEV-F steel was lower than that of the non-nitrided samples by nearly two orders of magnitude. The benefits of nitriding in the SAE XEV-F were two-fold: a) an increased surface hardness, and b) the prevention of NbC fracture and detachment, which results in even higher wear resistance.